Roseophilin-inspired derivatives as transmembrane anion carriers. Issue 9 (2nd September 2021) - Díaz-Cabrera, Sandra; Carreira-Barral, Israel; García-Valverde, María; Quesada, Roberto
ABSTRACT: Roseophilin is an alkaloid structurally related to prodiginines . The intriguing pharmacological properties of these derivatives have prompted us to prepare synthetic compounds 1 –3 inspired by their structure and to explore their transmembrane anion transport activity. The methoxyfuran heterocycle impacts the anionophoric activity of the compounds as a result of the reduced hydrogen-bonding ability and electrostatic repulsions between the oxygen in the furan ring and the anions. The position of the furan was also found to be crucial for determining their anion transport activity. Overall, replacement of the characteristic methoxypyrrole moiety of prodiginines and tambjamines by the methoxyfuran found in roseophilin is detrimental to their ability as anion carriers, suggesting that the biological activity of roseophilin is likely not related to their potential activity as anion carriers. Compound 2, bearing a furan ring attached to a dipyrromethene moiety, was found to be the most active anion carrier. GRAPHICAL ABSTRACT: uf0001